2008
DOI: 10.1007/s10600-008-9164-2
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition of the essential oil of Teucrium hyrcanicum and T. chamaedrys L. SUBSP. chamaedrys from Iran

Abstract: The genus Teucrium (Lamiaceae) is comprised of about 340 species widespread over the world. In the Flora Iranica, this genus is represented by 12 species [1]. Various species of the genus Teucrium are used as antiseptic, antipyretic, antiinflammatory, antispasmodic, antinociceptive, anti-rheumatic, anthelmintic, diuretic, hypoglycemic, diaphoretic, and tonic in folk medicine [2].Phytochemically, several diterpenoids, diterpenelactones, triterpenoids, flavonoids, and minor phenolic compounds have already been i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…These monoterpenes were reported as the main constituents in the oil of T. chamaedrys ssp. chamaedrys from Iran [ 6 ]. In this study, in relatively high percentages, essential oil from T. flavum contained α-pinene (10.5%), β -pinene (8.4%) and limonene (7.9%), while T. montanum essential oil contained β -pinene (12.3%) and limonene (4.6%).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These monoterpenes were reported as the main constituents in the oil of T. chamaedrys ssp. chamaedrys from Iran [ 6 ]. In this study, in relatively high percentages, essential oil from T. flavum contained α-pinene (10.5%), β -pinene (8.4%) and limonene (7.9%), while T. montanum essential oil contained β -pinene (12.3%) and limonene (4.6%).…”
Section: Resultsmentioning
confidence: 99%
“…T. stocksianum ssp. stocksianum [ 5 ], T. hyrcanicum [ 6 ], T. maghrebinum [ 7 ], T. montbtetii ssp. heliotropiifolium [ 8 ], T. scoridum [ 9 ] and T. salviastrum [ 4 ] have been previously investigated.…”
Section: Introductionmentioning
confidence: 99%
“…The oil of T. hyrcanicum comprised 3 monoterpenoids (8.3 %), 9 sesquiterpenoids (54.3 %) and 14 non-terpenoids (29.1 %). The essential oil of the flowering aerial parts of T. hyrcanicum was rich in sesquiterpenoids.In 2008, Kazemizadeh et al, reported hexahydrofarnesyl acetone (12.7 %), linalool (11.7 %) and (E)-β-farnesene (10.7 %), dihydroedulane (8.6 %) and ar-curcumene (8.5 %) as the main constituents of the essential oil of T. hyrcanicum1 . In another research, Kazemizadeh et al, reported chemical composition of the essential oils of two populations T. hyrcanicum in two different localities; hexahydrofarnesyl acetone (12.7 %), linalool (11.7 %) and (E)-β-farnesene (10.7 %) were the major components of the essential oil of T. hyrcanicum collected from Khalkhal-Asalem; (E)-β-farnesene (60.6 %) and (E)-α-farnesene (15.0 %) were the major components of the essential oil of T. hyrcanicum collected from Rostamabad 8 .…”
mentioning
confidence: 99%
“…T. halacsyanum Heldr. grows in the Eastern Mediterranean (Greece and Egypt) (3), while T. hyrcanicum L. is distributed in the region of Caucasus, Iran and Turkey (4).…”
Section: Introductionmentioning
confidence: 99%
“…The species of the genus Teucrium contain various secondary metabolites such as flavonoids, phenolic acids, tannins, bitter principles, essential oil, saponins, sterols, sugars and microelements that contribute to its biological activities (4)(5)(6)(7)(8). Many species of the genus are used in folk medicine as antidiabetics, diuretics, diaphoretics, expectorants, spasmolytics, antioxidants, antiseptics and stomachics (7,9).…”
Section: Introductionmentioning
confidence: 99%